Quantitative evaluation and factors of gas-wetness in gas/liquid/solid systems. Issue 4 (16th February 2016) - Jiang, G.; Zhang, M.; Xing, X.; Luo, S.; Zhou, L.; Xie, S.; Yang, Z.
ABSTRACT: After altering the wetness of porous media from preferentially liquid-wet to preferentially gas-wet, gas well production will increase greatly in gas condensate reservoirs. Since the gas-wet degree seriously affects the production, it has both theoretical and practical value to study quantitative measurement and effect factors for gas wettability. In the study, using the sessile drop and the captive bubble, the gas-wet quantitative evaluation methods and criteria have been put forward. Glass slides, treated by the fluorocarbon polymer Zonyl8740, were used as gas-wetness measurement substrates in order to eliminate the roughness effect. The calculation of slide surface free energy and slide/water interface free energy was determined by two models, respectively, Owens-Wendt and the captive bubble two-probe method. The results show that, if the solid surface free energy is less than solid/liquid interface free energy, the surface or the interface will be preferential gas-wetting, otherwise, non gas-wetting; with the decrease of surface free energy and interface free energy, the gas-wetting gets strong. Thus, it is effective to realize gas-wetness by lowering the value of surface free energy or surface tension.